“Neither Innocent, nor Guilty”: the Scapegoat in the Ironic Short Stories of William Somerset Maugham - Klečková, Maria (American & British Studies Annual, 2020)
This article aims to examine several short stories of W. Somerset Maugham in terms of ironic victimization. Northrop Frye’s claim that a pharmakos or a scapegoat is a typical ironic victim inspired my idea of dissecting a number of characters in Maugham’s stories as pharmakoi. In the analysis two types of pharmakoi characters were discovered: primary and secondary ones, with each implying a different targeting of irony. Primary pharmakoi are disguised as scapegoat characters, but it is through the contact with them that the real victim of irony is revealed. The stories these characters are featured in are usually more complex, and the irony is built either on a stereotype or an archetype. The stereotype proposes the thematical background on which the irony is built, while the archetype – here a structural model – is based on the readers’ subconscious expectations. In secondary scapegoat stories, irony is targeted at one of the characters or the community they stereotypically represent. Several short stories are analysed in the article: “The Mother,” “The Fall of Edward Barnard,” “The Alien Corn” and “Rain.”